Bronchial Fistula and Pneumomediastinum after EBUS-TBNA Following Mediastinoscopy - Bougioukas, Ioannis; Seipelt, Ralf; Huwer, Hanno (The Thoracic and Cardiovascular Surgeon Reports, 2019)
Background Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a very useful diagnostic tool for the assessment of enlarged mediastinal and hilar lymph nodes. It is a safe procedure with a low risk of complications.Case Description We report a case of bronchial fistula and pneumomediastinum after EBUS-TBNA, which was performed shortly after a mediastinoscopy. Due to the extent of the bronchial lesion, a surgical closure of the bronchial fistula was necessary. The patient recovered completely.Conclusion The performance of EBUS-TBNA shortly after a mediastinoscopy should not be recommended to avoid possible procedure-related complications.
Keywords: mediastinum (incl. mediastinoscopy); thoracic surgery; mediastinal lymph nodes; ultrasound (all applications)